PENGARUH PROMOSI INSTAGRAM TERHADAP MINAT BELI DI AMANI COFFEE & EATERY, KEC. ADIWERNA, KAB. TEGAL - Pangesti, Silvi Yuni; Hamdanur, Peris; Wahyudi, Dedy (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This study aims to examine the influence of Instagram-based social media promotion on consumer purchase intention at Amani Coffee & Eatery, located in Adiwerna District, Tegal Regency. The research is motivated by the increasing use of Instagram as a promotional platform and the intensifying competition in the culinary business sector. A descriptive quantitative method was employed, with data collected through questionnaires distributed to 100 respondents who are followers of the @Amani.cf Instagram account and active consumers. The Instagram promotion variable was analyzed through four dimensions: context, communication, collaboration, and connection. Meanwhile, the purchase intention variable includes transactional, referential, preferential, and exploratory intentions. The results of the simple linear regression analysis indicate that Instagram promotion has a positive and significant influence on consumer purchase intention. These findings affirm that attractive, communicative, and consistent content strategies can enhance audience engagement and purchasing decisions. This research offers important implications for culinary business actors in designing effective digital promotion strategies tailored to local consumer characteristics